Pipeline failures in corrosive environments - A conceptual analysis of trends and effects - Ossai, C.; Boswell, B.; Davies, Ian (Elsevier Ltd, 2015)
© 2015 Elsevier Ltd. Pipeline corrosion is a major challenge facing many oil and gas industries today because of the enormous downtime associated with corrosion related failures. Fatigue stress initiation in pipelines has been attributed to corrosion defects whose growth is enhanced by cyclic loading caused by the operating pressure of the transported fluids. This work reviews the concept of oil and gas transmission pipeline failures in corrosive environment by highlighting the corrosion mechanisms, dominant stress corrosion cracking trends, hydrogen induced cracking and predominant models for burst pressure estimation. Fatigue stress failure trends of corroding pipelines were also explained whilst describing some pipeline manufacturing processes that increases the susceptibility to fatigue stress failure. Optimization framework for pipeline integrity assurance against corrosion fatigue failures was also shown to incorporate different steps that includes - strategic policy initiation, policy implementation, information analysis and reviews and implementation actions.